1996
DOI: 10.1192/bjp.168.1.49
|View full text |Cite
|
Sign up to set email alerts
|

A One Year Prospective Study of the Effect of Life Events and Medication in the Aetiology of Schizophrenic Relapse

Abstract: A contribution of life events to the risk of relapse in schizophrenia was confirmed by this study but the hypothesis that life events trigger relapse was not supported, nor was the hypothesis that life events are more relevant to relapse in patients on maintenance medication than in patients off medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(48 citation statements)
references
References 19 publications
4
43
0
1
Order By: Relevance
“…3). Individual variation in minimum dose required in relapse-free maintenance treatment is also difficult to assess, because, in typical cases, relapse does not occur immediately on withdrawal or on dose reduction, but in a probabilistic fashion, sometime in the next year or two [39,54,58,60,69,90,111]. This principle also applies to atypical antipsychotic drugs [47,157].…”
Section: Neuroleptic-resistant Psychosis and Individual Differences mentioning
confidence: 99%
“…3). Individual variation in minimum dose required in relapse-free maintenance treatment is also difficult to assess, because, in typical cases, relapse does not occur immediately on withdrawal or on dose reduction, but in a probabilistic fashion, sometime in the next year or two [39,54,58,60,69,90,111]. This principle also applies to atypical antipsychotic drugs [47,157].…”
Section: Neuroleptic-resistant Psychosis and Individual Differences mentioning
confidence: 99%
“…The association of stressful life events (Hirsch et al, 1996) and stressful home environments (Kuipers & Bebbington, 1988) with relapse among people with schizophrenia adds weight to this model and its predictions.…”
Section: Cognitive-behavioural Interventionsmentioning
confidence: 99%
“…The association between stressful life events and onset and relapse of schizophrenia has been shown previously (Day et al, 1987;Ventura et al, 1989;Malla et al, 1990;Hirsch et al, 1996). Rather than simply peaking in the few weeks before a relapse and acting merely as a trigger, it has been reported that an increased rate of life events occur over a more lengthy period before the onset of psychosis (McDonald and Murray, 2000).…”
Section: Discussionmentioning
confidence: 89%
“…The earliest of these are complications of pregnancy and birth, while late environmental risk factors have been identified as immigrant status, chronic cannabis abuse, and adverse life events (McDonald and Murray, 2000). Many studies have reported an excess of stressful life events in the few weeks before the onset or relapse of schizophrenia (Day et al, 1987;Ventura et al, 1989;Malla et al, 1990;Hirsch et al, 1996). The fine-tuning of the brain connections under the influence of stress and hormones may ultimately lead to neurodegeneration, loss of brain mass, and overt psychosis (Tsuang, 2000).…”
Section: Introductionmentioning
confidence: 98%